Higgs Model Coupled to Dark Photons - Gamboa-Rios, J; Pino-Rozas, M (World Scientific, 2015)
A dark sector containing a Higgs field and a dark photon coupled to visible photons via a small kinetic mixing is considered. The mass of the dark gauge boson becomes rescaled by the parameter involved in the kinetic mixing. We also calculate the total annihilation cross-section for scalar Higgs interacting with an external field and show that exhibits Sommerfeld enhancement. The model can be extended to a SU(3) × SU(2) × U(1) dark sector. The mass of the dark Z boson increases due to the kinetic mixing. © 2015 World Scientific Publishing Company.